Ganoderma lucidum extract inhibits proliferation of SW 480 human colorectal cancer cells - Xie, J.T.; Wang, C.Z.; Wicks, S.; Yin, J.J.; Kong, J.; Li, J.; Li, Y.C.; Yuan, C.S. (Experimental Oncology, 2006)
Aim: Ganoderma lucidum is a commonly used Chinese herb and an important ingredient in traditional Chinese medicine herbal formulations for immune dysfunction related illnesses. The effects of this medicinal mushroom on human colorectal cancer cells have not yet been evaluated. In this study, we investigated the effects of Ganoderma lucidum extract using SW 480 human colorectal cancer cell line. Materials and Methods: Two different fractions of Ganoderma lucidum extract, i.e., a fraction containing mainly polysaccharides (GLE-1), and a triterpenoid fraction without polysaccharides (GLE-2) were analyzed. Their antiproliferative activity was evaluated by cell proliferation assay and 3H-thymidine incorporation assay. Scavenging effects of DPPH radical were assessed using ESR-spectroscopy. Results: Our data showed that both GLE-1 and GLE-2 significantly inhibited the proliferation of SW 480 cells. The inhibitory effect of GLE-2 was much stronger than that of GLE-1. GLE-1 inhibited DNA synthesis in the cells and reduced the formation of DPPH radicals. Conclusion: Ganoderma lucidum extract inhibits proliferation of human colorectal cancer cells and possesses antioxidant properties. Цель: для лечения заболеваний, связанных с нарушениями функционирования иммунной системы, в традиционной китайской медицине часто используют препараты на основе Ganoderma lucidum. В данной работе было изучено влияние экстракта Ganoderma lucidum на клетки колоректального рака человека линии SW 480. Материалы и методы: изучали две фракции экстракта Ganoderma lucidum: фракцию GLE-1, содержащую полисахариды, и тритерпеноидную фракцию GLE-2. Их рост-ингибирующую активность определяли с помощью анализа клеточной пролиферации и по включению 3 H-тимидина. Для оценки антиоксидантной активности использовали ЕСР-спектроскопию. Результаты: обе фракции Ganoderma lucidum подавляли пролиферацию клеток SW 480. Рост-ингибирующий эффект GLE-2 был более выраженным, чем фракции GLE-1. Фракция GLE-1 подавляла синтез ДНК в клетках линии SW 480 и понижала уровень формирования DPPH радикалов. Выводы: экстракт Ganoderma lucidum подавляет пролиферацию клеток колоректального рака человека и обладает антиоксидантными свойствами.